Primary partial solid-waste recovery in small urban centers of population - Medina, Alberto; Gutiérrez, Edixon (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
This paper tackles the problem of solid waste in small centers of population, based on a techno-economic study carried out on a partial prymary recovery process for paper of aluminum and glass in Punta Cardón, State of Falcón, Venezuela. Date was gathered on the amount of waste recovered after due classification in each house and subsequent colletion. Data were also obtained on the operational process, as well as on how it affects the trash collection service. Calculations were then made in order to obtain the general management macro indicators: efficiency, coverage, costs and other comparative items, as well as the point of equilibrium of the process. lt was concluded that, from the economic point of view, the partial primary recovery process is profitable only after it reaches a recovery percentage equivalent to the point of equilibrium given by the cost-revenue ratio. This creates a direct relationship between the active participation of the population and the success of the process. The process is an excellent auxiliary system for managing solid waste in a small town.